High-strength regenerated silk fibroin material and preparation method thereof

Through gradient alcohol treatment and vacuum drying post-treatment methods, chemical crosslinked silk fibroprotein hydrogel is processed to form a dual crosslinking network structure, which solves the problem of insufficient mechanical strength of existing materials and realizes the preparation of high-strength regenerated silk fibroprotein materials, which is suitable for the biomedical field.

CN119842098AActive Publication Date: 2025-04-18DONGHUA UNIV

Patent Information

Application Number
CN202411443125.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-04-18
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing regenerated silk fibroin materials are difficult to meet the mechanical strength requirements in the repair and treatment of load-bearing and stress-bearing tissues, and the processing and forming conditions are harsh and the cost is high, which limits its wide application in the field of biomedical science.

Method used

The chemical crosslinked silk fibroprotein hydrogel is treated by gradient alcohol treatment and vacuum drying post-treatment method to form a dual crosslinking network structure to improve the compression modulus and mechanical properties of the material.

Benefits of technology

The high-strength regenerated silk fibroprotein material has been prepared, with a compression modulus of ≥0.2GPa, which is both biocompatible and degradable, and is suitable for hard tissue biomedical materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842098A_ABST
    Figure CN119842098A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedicine, and particularly relates to a high-strength regenerated silk fibroin material and a preparation method thereof.The preparation method specifically comprises the step that chemical crosslinking silk fibroin hydrogel is sequentially subjected to gradient alcohol treatment and vacuum drying treatment, and the high-strength regenerated silk fibroin material is obtained, the gradient alcohol treatment refers to staged treatment by adopting an ethanol aqueous solution, the concentration of the ethanol aqueous solution in each stage is fixed, and the concentrations of the ethanol aqueous solutions in different stages are increased along with the increase of stage serial numbers; the finally prepared high-strength regenerated silk fibroin material has a double-cross-linked network structure, and the double-cross-linked network structure is formed by intertwining a silk fibroin chemical cross-linked network and a beta folding structure physical cross-linked network. The preparation method disclosed by the invention is simple and easy to implement, and the compression mechanical property (the compression modulus is greater than or equal to 0.2 GPa) of the regenerated silk fibroin material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedicine, and in particular relates to a high-strength regenerated silk fibroin material and a preparation method thereof. Background Art

[0002] Silk fibroin (SF) is a natural amino acid polymer with excellent physical and chemical properties, and has excellent biocompatibility, degradability, processability and flexibility. It has broad application prospects in the biomedical field. Silk fibroin raw materials are usually obtained by degumming silk cocoons to remove the sericin covering the surface, and then regenerated and processed into a variety of regenerated silk fibroin (RSF) materials for use, such as silk fibroin microspheres, fibers, films, hydrogels, three-dimensional scaffolds, etc. However, due to the mindset of the soft properties of natural silk fibroin and the limitations of conventional regeneration processes and processes, the developed RSF materials often cannot obtain high mechanical strength (such as compression modulus). This makes it difficult to meet the repair and treatment needs of load-bearing tissues, which in turn limits the scope of application of RSF materials in biomedicine and other fields to a certain extent.

[0003] In recent years, a small number of cutting-edge reports have conducted exploratory research in related fields. Since a considerable portion of regenerated silk fibroin materials have obvious water-soluble properties in the early stage, certain pretreatment is usually required to give them "water-insoluble" properties for subsequent use in aqueous environments. The more easily conceivable strategy is to first use a high concentration of alcohol treatment to make it "water-insoluble". At the same time, such treatment methods will also bring about a certain degree of improvement in mechanical properties. For example, the patent (publication number: CN109999227A) first used 100% ethanol to treat the composite electrospun fibers of silk fibroin and chitin to obtain a silk fibroin-based nanofiber scaffold that can be stably used in an aqueous environment. The literature (Enhancing Mechanical Properties of Silk Fibroin Hydrogel through Restricting the Growth of β-Sheet Domains [J]. ACS Applied Materials & Interfaces, 2017, 9 (20): 17489-17498.) prepared a silk fibroin hydrogel with excellent strength by treating peroxidase cross-linked silk fibroin hydrogel with 90% ethanol, and the compression modulus can reach 3MPa. Similarly, the literature (Engineering biomimetic silk fibroin hydrogel scaffolds with "organic-inorganic assembly" strategy for rapid bone regeneration [J]. Bioactive Materials, 2024, 40: 541-556.) treated methacrylylated silk fibroin chemical cross-linked hydrogel with 100% ethanol to obtain a silk fibroin hydrogel material with a compression modulus of 2.33MPa.Although the compression modulus of the materials obtained by this type of processing method (reference (Scaffolds for bone-tissue engineering[J].Matter,2022,5(9):2722-2759), reference (Scaffold Fabrication Technologies and Structure / FunctionProperties in Bone Tissue Engineering[J].Advanced Functional Materials,2021,31:2010609.), reference (Biomimetic porous scaffolds for bone tissue engineering[J].Materials Science and Engineering:R:Reports,2014,80:1-36.)) is significantly improved compared with the RSF materials prepared by traditional methods, it is still difficult to meet the ideal requirements (0.1-2GPa) for load-bearing tissue repair and treatment. In addition, the literature (Thermoplastic moulding of regenerated silk[J].Nature Materials,2020,19:102–108.) prepared high-strength silk fibroin materials by combining high temperature with ultra-high pressure molding, that is, using silk fibroin ground powder raw materials to perform hot pressing molding under high temperature and ultra-high pressure (145°C, 632MPa) to prepare high-strength silk fibroin materials with a compression modulus of up to 3GPa. However, the processing and molding conditions of such regenerated silk fibroin materials are extremely harsh, and the processing costs are significantly increased, which is not conducive to large-scale production and promotion.

[0004] In summary, there is still a lack of a simple and easy method for preparing high-strength regenerated silk fibroin materials to meet their needs in the fields of repair and treatment of load-bearing tissues. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a high-strength regenerated silk fibroin material and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a high-strength regenerated silk protein material, comprising: subjecting a chemically cross-linked silk protein hydrogel to a gradient alcohol treatment and a vacuum drying treatment in sequence to obtain the high-strength regenerated silk protein material, wherein the gradient alcohol treatment refers to a staged treatment using an ethanol aqueous solution, wherein the concentration of the ethanol aqueous solution in each stage is fixed, and the concentration of the ethanol aqueous solution in different stages increases as the stage number increases.

[0008] As the preferred technical solution:

[0009] In the method for preparing a high-strength regenerated silk fibroin material as described above, the compression modulus of the chemically cross-linked silk fibroin hydrogel is ≥1KPa, and the compression modulus of the high-strength regenerated silk fibroin material is ≥0.2GPa.

[0010] The method for preparing a high-strength regenerated silk protein material as described above is divided into at least two stages, the volume concentration of the ethanol aqueous solution is 10% to 100%, the treatment time of each stage is 1 to 3 hours, and the treatment temperature is 25 to 37°C.

[0011] In the method for preparing a high-strength regenerated silk fibroin material as described above, the volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage is 1:10-50.

[0012] In the method for preparing a high-strength regenerated silk fibroin material as described above, the vacuum drying treatment temperature is 25 to 37° C., the air pressure is ≤2 KPa, and the time is 8 to 24 hours.

[0013] As described above, a method for preparing a high-strength regenerated silk fibroin material, the preparation process of chemically cross-linked silk fibroin hydrogel is as follows: after adding LAP (phenyl-2,4,6-trimethylbenzoylphosphite lithium salt) solution to SFMA (methacrylylated silk fibroin) solution, ultraviolet light is cured to form a gel, thereby obtaining chemically cross-linked silk fibroin hydrogel (SFMA hydrogel, silk fibroin is chemically modified and then other functional groups are introduced to cross-link into a gel).

[0014] According to the method for preparing a high-strength regenerated silk fibroin material, the concentration of the SFMA solution is 10-20wt%, the concentration of the LAP solution is 2wt%, the mass ratio of the SFMA solution to the LAP solution is 1:0.1-0.3, the UV curing time is 2-5min, and the UV intensity is 20-50mW / cm 2 , the curing temperature is 25 ~ 37 ℃.

[0015] As described above, a method for preparing a high-strength regenerated silk fibroin material, the preparation process of chemically cross-linked silk fibroin hydrogel is as follows: after adding Ru (tri(2,2'-bipyridine)dichlororuthenium(II) hexahydrate) solution and SPS (sodium persulfate) solution to SF (silk fibroin) solution in sequence, the solution is cured into gel by visible light to obtain chemically cross-linked silk fibroin hydrogel (SF hydrogel, the functional groups of the amino acids of silk fibroin itself are cross-linked into gel).

[0016] According to the method for preparing a high-strength regenerated silk fibroin material, the concentration of the SF solution is 10-20wt%, the concentration of the Ru solution is 0.03-0.07mol / L, the concentration of the SPS solution is 0.3-0.7mol / L, the volume ratio of the SF solution concentration to the Ru solution is 20-100:1, the volume ratio of the Ru solution to the SPS solution is 1:0.8-1.2, the visible light curing time is 5-30min, and the visible light intensity is 20-50mW / cm 2 , the curing temperature is 25 ~ 37 ℃.

[0017] The high-strength regenerated silk protein material prepared by the preparation method of a high-strength regenerated silk protein material as described in any of the above items has a double cross-linked network structure, and the double cross-linked network structure is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0018] Principle of the invention:

[0019] The present invention is based on chemically cross-linked silk fibroin hydrogel and further innovatively utilizes gradient alcohol treatment and vacuum drying post-treatment to achieve the preparation of high-strength regenerated silk fibroin material.

[0020] First, a silk fibroin hydrogel is constructed based on a chemical cross-linking strategy to form a regenerated silk fibroin material with a three-dimensional chemical cross-linking network structure. For example, an enzyme / non-enzymatic cross-linking system is used to induce the characteristic functional groups (such as phenolic hydroxyl groups) retained in the natural silk fibroin molecules to react to form a three-dimensional cross-linking network; or a characteristic cross-linking group (such as a carbon-carbon double bond) is first introduced into the natural silk fibroin molecules based on a chemical modification method, and then a corresponding reaction strategy is used to form a three-dimensional cross-linking network structure.

[0021] The silk hydrogel formed by chemical cross-linking is further treated with gradient alcohol to transform the loose α-helix conformation in the silk protein material into a dense β-fold conformation (crystalline structure). Unlike a single high-concentration ethanol treatment, this patent innovatively introduces gradient alcohol treatment (changing from low concentration to high concentration) to make the conformational transition process of the silk protein molecules relatively mild, and a relatively synchronous and uniform conformational transition occurs from the inside to the outside. This ensures that the cross-linked network and other structures inside the hydrogel (including the chemical cross-linked network and the physical cross-linked network formed by the β-folded conformation) are more uniform, and the overall shrinkage of the hydrogel is also more uniform, ultimately resulting in the material's appearance morphological characteristics having good conformability and significantly improved overall mechanical properties. The specific principle includes: when the hydrogel is immersed in a low concentration of alcohol aqueous solution, the water molecules in the alcohol aqueous solution first enter the hydrogel to expand the hydrogel, making it easier for the alcohol molecules to enter the hydrogel, so that the internal silk protein molecular chain can also be fully in contact with the alcohol, ensuring the uniformity of the internal and external microenvironments; the low concentration of alcohol treatment in the early stage does not bring about a rapid conformational change of silk protein, and thus also provides conditions for the entry of alcohol molecules under medium or high concentration conditions in the later stage; when the hydrogel is gradually immersed in an alcohol aqueous solution with a higher alcohol concentration, the conformational change of the silk protein molecules will gradually accelerate. However, since the microenvironment inside and outside the material is relatively uniform, this will cause the conformational change of different parts of the material to occur more uniformly, and the contraction of different parts of the material will also become more consistent. On the contrary, if the hydrogel is directly immersed in a high concentration of alcohol aqueous solution, the high concentration of alcohol will cause the surface part of the hydrogel to undergo a rapid conformational change and generate a relatively dense β-folded crystalline structure, which will inevitably block the further entry of subsequent alcohol molecules, thus causing the occurrence of uneven conformational change and material contraction, which is not conducive to a substantial improvement in the mechanical properties of the material.

[0022] Subsequently, the material is further treated by vacuum drying, so that a large number of alcohol molecules and a small amount of water on the surface and inside are removed more uniformly under relatively mild external conditions. In this process, different parts of the material further shrink uniformly, and finally a high-strength regenerated silk protein material is prepared. The specific principle is as follows: vacuum drying post-treatment is carried out under relatively mild room temperature conditions. In addition, vacuum conditions are conducive to the simultaneous removal of alcohol molecules and a small amount of water inside and on the surface of the material under relatively uniform conditions, thereby ensuring the uniformity of solvent removal and material shrinkage in various parts. If high-temperature drying or room temperature drying is used for post-treatment, since the ethanol on the surface of the material is easily removed first, the rapid removal of the surface solvent is likely to cause the surface of the material to shrink rapidly and become denser, which will increase the difficulty of removing the internal solvent, and will also cause uneven shrinkage of different parts of the material and solvent volatilization. This will lead to an increase in the anisotropic characteristics of the material and a decrease in the mechanical strength of the material. If freeze-drying is used directly for post-processing, the anisotropic characteristics of the internal pore structure will be significantly enhanced due to the formation and disappearance of "ice crystals" involved in the freezing and sublimation process, thereby significantly reducing the mechanical strength of the material.

[0023] In summary, on the basis of the formation of the three-dimensional chemical cross-linked network of silk fibroin material, further gradient alcohol treatment and vacuum drying post-treatment jointly guarantee the regular and uniform formation of the β-folded crystal structure inside the material and the uniform shrinkage of all parts of the material to the greatest extent. The formation of the structure and the reduction of the anisotropic characteristics of the material comprehensively guarantee the preparation of high-strength silk fibroin material. In addition, it can be expected that by using relevant process flows, by introducing reinforcing fillers into such silk fibroin system, or by introducing other substances to bring about enhanced chemical or physical cross-linked networks, it is expected to obtain composite modified materials with better comprehensive mechanical properties.

[0024] Beneficial effects:

[0025] (1) A method for preparing a high-strength regenerated silk fibroin material of the present invention has a simple and easy preparation process and low cost. In the preparation process, the steps of gradient alcohol treatment and vacuum drying post-treatment are used, which are conducive to forming a relatively regular and uniform crystalline structure, and can effectively avoid the appearance of anisotropic structure and anisotropic shrinkage of the silk fibroin material to a large extent, and significantly improve the compressive mechanical properties of the regenerated silk fibroin material (compression modulus ≥ 0.2GPa).

[0026] (2) The high-strength regenerated silk fibroin material of the present invention has both excellent biocompatibility and biodegradability, and has good application prospects in the field of hard tissue biomedical materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1The macroscopic comparison diagram of the regenerated silk fibroin material obtained after single concentration alcohol treatment (Comparative Example 1) and gradient alcohol treatment (Example 1) (both post-treatments are vacuum drying). In the figure, (a) is Comparative Example 1, and (b) is Example 1. It can be seen that gradient alcohol treatment + vacuum drying post-treatment can obtain uniform material shrinkage;

[0028] Figure 2 The internal structure comparison diagram of the regenerated silk fibroin material obtained after single concentration alcohol treatment (Comparative Example 1) and gradient alcohol treatment (Example 1) (all post-treatments are vacuum drying). In the figure, (a) is Comparative Example 1, and (b) is Example 1. It can be seen that the gradient alcohol treatment + vacuum drying post-treatment can obtain the regenerated silk fibroin material with a denser and more uniform internal structure. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0030] The detection method of compression modulus in the following text is: use INSTRON / 5969 electronic universal material testing machine to perform static compression test on the test material. The specific test method is: adjust the upper and lower clamps so that the clamps are just in contact with the test material, and then compress the test material at a compression rate of 10mm / min until the test material breaks, obtain the stress-strain data of the test material at different time points, select the area with a strain of 0%-5% in the stress-strain curve for linear fitting, and calculate the compression modulus of the test material.

[0031] Example 1

[0032] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0033] (1) Prepare raw materials:

[0034] SFMA solution: concentration is 15wt%, solvent is deionized water;

[0035] LAP solution: concentration is 2wt%, solvent is deionized water;

[0036] Ethanol aqueous solution;

[0037] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0038] After adding LAP solution to SFMA solution (mass ratio of 1:0.1), the UV light intensity was 30 mW / cm 2, UV curing at 25°C for 5 minutes to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 3 KPa;

[0039] (3) Preparation of high-strength regenerated silk fibroin:

[0040] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:50, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0041] The volume concentration of the ethanol aqueous solution in stage 1 is 20%, the treatment time is 1.5 h, and the treatment temperature is 25°C;

[0042] The volume concentration of the ethanol aqueous solution in stage 2 is 40%, the treatment time is 1.5 h, and the treatment temperature is 25°C;

[0043] The volume concentration of the ethanol aqueous solution in stage three is 60%, the treatment time is 1.5 h, and the treatment temperature is 25°C;

[0044] In stage 4, the volume concentration of the ethanol aqueous solution is 80%, the treatment time is 1.5 h, and the treatment temperature is 25° C.;

[0045] In stage five, the volume concentration of the ethanol aqueous solution is 100%, the treatment time is 3 h, and the treatment temperature is 25° C.;

[0046] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 2 KPa and a temperature of 25°C for 12 hours to obtain a high-strength regenerated silk fibroin material.

[0047] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.3GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0048] Comparative Example 1

[0049] A method for preparing a regenerated silk fibroin material is basically the same as that in Example 1, except that the volume concentration of the ethanol aqueous solution used in stages 1 to 5 of this comparative example is the same, i.e., 100%.

[0050] The compression modulus of the regenerated silk protein material finally obtained is 152MPa, and it has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0051] Comparing Comparative Example 1 with Example 1, it can be seen that the compression modulus of the regenerated silk fibroin material prepared in Comparative Example 1 is significantly reduced. The reason for this difference is that the chemically cross-linked silk fibroin hydrogel in Comparative Example 1 is directly immersed in a high concentration of pure ethanol, while Example 1 adopts a gradient progressive immersion method; due to direct immersion in high concentration ethanol, the surface of the chemically cross-linked silk fibroin hydrogel in Comparative Example 1 rapidly undergoes a conformational change to form a dense structure. This rapidly formed dense structure hinders the subsequent alcohol molecules from further penetrating into the interior of the chemically cross-linked silk fibroin hydrogel, resulting in an uneven conformational change of the hydrogel material as a whole (such as Figure 1 , Figure 2 As shown in Example 1, this uneven conformational transition increases the anisotropy of the internal structure, so that the compression modulus of the finally obtained regenerated silk fibroin material is not as good as that in Example 1.

[0052] Comparative Example 2

[0053] A method for preparing a regenerated silk fibroin material is basically the same as that in Example 1, except that natural drying is used in place of vacuum drying in Example 2.

[0054] The compression modulus of the regenerated silk protein material finally obtained is 79MPa, and it has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0055] Compared with Example 1, it can be seen that the compression modulus of the regenerated silk fibroin material obtained in Comparative Example 2 is significantly reduced. The reason for this difference is that Comparative Example 2 adopts a natural drying method. During the drying process, the ethanol on the surface of the silk fibroin material is easily evaporated and removed quickly, causing the surface of the silk fibroin material to shrink rapidly and become denser. This change increases the difficulty of removing the solvent inside the silk fibroin material, resulting in uneven shrinkage and solvent volatilization in different parts of the silk fibroin material, thereby increasing the anisotropic characteristics of the regenerated silk fibroin material obtained and reducing the compression modulus.

[0056] Example 2

[0057] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0058] (1) Prepare raw materials:

[0059] SFMA solution: concentration is 20wt%, solvent is deionized water;

[0060] LAP solution: concentration is 2wt%, solvent is deionized water;

[0061] Ethanol aqueous solution;

[0062] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0063] After adding LAP solution to SFMA solution (mass ratio of 1:0.3), the UV light intensity was 50 mW / cm 2 , UV curing at 30°C for 20 minutes to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 27 KPa;

[0064] (3) Preparation of high-strength regenerated silk fibroin:

[0065] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:50, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0066] In stage 1, the volume concentration of the ethanol aqueous solution is 20%, the treatment time is 2 h, and the treatment temperature is 37°C;

[0067] In stage 2, the volume concentration of the ethanol aqueous solution is 40%, the treatment time is 2 h, and the treatment temperature is 37°C;

[0068] In stage 3, the volume concentration of the ethanol aqueous solution is 60%, the treatment time is 2 h, and the treatment temperature is 37°C;

[0069] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 1 KPa and a temperature of 30°C for 24 hours to obtain a high-strength regenerated silk protein material.

[0070] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.33GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0071] Example 3

[0072] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0073] (1) Prepare raw materials:

[0074] SFMA solution: concentration is 15wt%, solvent is deionized water;

[0075] LAP solution: concentration is 2wt%, solvent is deionized water;

[0076] Ethanol aqueous solution;

[0077] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0078] After adding LAP solution to SFMA solution (mass ratio of 1:0.2), the UV light intensity was 50 mW / cm 2 , UV curing at 37°C for 20 min to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 10 KPa;

[0079] (3) Preparation of high-strength regenerated silk fibroin:

[0080] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:20, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0081] In stage 1, the volume concentration of the ethanol aqueous solution is 10%, the treatment time is 2 h, and the treatment temperature is 30°C;

[0082] The volume concentration of the ethanol aqueous solution in stage 2 is 30%, the treatment time is 2 h, and the treatment temperature is 30°C;

[0083] In stage three, the volume concentration of the ethanol aqueous solution is 50%, the treatment time is 2 h, and the treatment temperature is 30°C;

[0084] In stage 4, the volume concentration of the ethanol aqueous solution is 70%, the treatment time is 2 h, and the treatment temperature is 30° C.;

[0085] In stage five, the volume concentration of the ethanol aqueous solution is 90%, the treatment time is 2 h, and the treatment temperature is 30° C.;

[0086] The volume concentration of the ethanol aqueous solution in stage six is ​​100%, the treatment time is 2 hours, and the treatment temperature is 30°C;

[0087] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 2 KPa and a temperature of 37°C for 8 hours to obtain a high-strength regenerated silk fibroin material.

[0088] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.28GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0089] Example 4

[0090] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0091] (1) Prepare raw materials:

[0092] SFMA solution: concentration is 10wt%, solvent is deionized water;

[0093] LAP solution: concentration is 2wt%, solvent is deionized water;

[0094] Ethanol aqueous solution;

[0095] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0096] After adding LAP solution to SFMA solution (mass ratio of 1:0.1), the UV light intensity was 20 mW / cm 2 , UV curing at 37°C for 30 min to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 1 KPa;

[0097] (3) Preparation of high-strength regenerated silk fibroin:

[0098] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:10, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0099] In stage 1, the volume concentration of the ethanol aqueous solution is 10%, the treatment time is 3 h, and the treatment temperature is 37°C;

[0100] In stage 2, the volume concentration of the ethanol aqueous solution is 80%, the treatment time is 3 h, and the treatment temperature is 37°C;

[0101] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 2 KPa and a temperature of 25°C for 8 hours to obtain a high-strength regenerated silk protein material.

[0102] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.21GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0103] Example 5

[0104] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0105] (1) Prepare raw materials:

[0106] SF solution: concentration is 15wt%, solvent is deionized water;

[0107] Ru solution: concentration is 0.05 mol / L, the solvent is deionized water;

[0108] SPS solution: concentration is 0.5 mol / L, the solvent is deionized water;

[0109] Ethanol aqueous solution;

[0110] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0111] After Ru solution and SPS solution were added to SF solution in sequence, the visible light intensity was 30 mW / cm 2 , curing under visible light at 30°C for 20 min to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 13 KPa;

[0112] Among them, the volume ratio of SF solution concentration to Ru solution is 20:1, and the volume ratio of Ru solution to SPS solution is 1:1;

[0113] (3) Preparation of high-strength regenerated silk fibroin:

[0114] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:50, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0115] The volume concentration of the ethanol aqueous solution in stage 1 is 20%, the treatment time is 1.5 h, and the treatment temperature is 25°C;

[0116] The volume concentration of the ethanol aqueous solution in stage 2 is 40%, the treatment time is 1.5 h, and the treatment temperature is 25°C;

[0117] The volume concentration of the ethanol aqueous solution in stage three is 60%, the treatment time is 1.5 h, and the treatment temperature is 25°C;

[0118] In stage 4, the volume concentration of the ethanol aqueous solution is 80%, the treatment time is 1.5 h, and the treatment temperature is 25° C.;

[0119] In stage five, the volume concentration of the ethanol aqueous solution is 100%, the treatment time is 3 h, and the treatment temperature is 25° C.;

[0120] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 2 KPa and a temperature of 25°C for 12 hours to obtain a high-strength regenerated silk fibroin material.

[0121] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.27GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0122] Example 6

[0123] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0124] (1) Prepare raw materials:

[0125] SF solution: concentration is 10wt%, solvent is deionized water;

[0126] Ru solution: concentration is 0.07 mol / L, the solvent is deionized water;

[0127] SPS solution: concentration is 0.7 mol / L, the solvent is deionized water;

[0128] Ethanol aqueous solution;

[0129] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0130] After Ru solution and SPS solution were added to SF solution in sequence, the visible light intensity was 20 mW / cm 2 , curing under visible light at 25°C for 5 minutes to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 12 KPa;

[0131] Among them, the volume ratio of SF solution concentration to Ru solution is 30:1, and the volume ratio of Ru solution to SPS solution is 1:0.8;

[0132] (3) Preparation of high-strength regenerated silk fibroin:

[0133] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:50, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0134] In stage 1, the volume concentration of the ethanol aqueous solution is 20%, the treatment time is 2 h, and the treatment temperature is 37°C;

[0135] In stage 2, the volume concentration of the ethanol aqueous solution is 40%, the treatment time is 2 h, and the treatment temperature is 37°C;

[0136] In stage 3, the volume concentration of the ethanol aqueous solution is 60%, the treatment time is 2 h, and the treatment temperature is 37°C;

[0137] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 1 KPa and a temperature of 30°C for 24 hours to obtain a high-strength regenerated silk protein material.

[0138] The final high-strength regenerated silk protein material has a compression modulus of 0.22GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0139] Example 7

[0140] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0141] (1) Prepare raw materials:

[0142] SF solution: concentration is 20wt%, the solvent is deionized water;

[0143] Ru solution: concentration is 0.07 mol / L, the solvent is deionized water;

[0144] SPS solution: concentration is 0.7 mol / L, the solvent is deionized water;

[0145] Ethanol aqueous solution;

[0146] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0147] After Ru solution and SPS solution were added to SF solution in sequence, the visible light intensity was 50 mW / cm 2 , curing under visible light at 37°C for 30 min to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 21 KPa;

[0148] Among them, the volume ratio of SF solution concentration to Ru solution is 20:1, and the volume ratio of Ru solution to SPS solution is 1:1.2;

[0149] (3) Preparation of high-strength regenerated silk fibroin:

[0150] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:20, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0151] In stage 1, the volume concentration of the ethanol aqueous solution is 10%, the treatment time is 2 h, and the treatment temperature is 30°C;

[0152] The volume concentration of the ethanol aqueous solution in stage 2 is 30%, the treatment time is 2 h, and the treatment temperature is 30°C;

[0153] In stage three, the volume concentration of the ethanol aqueous solution is 50%, the treatment time is 2 h, and the treatment temperature is 30°C;

[0154] In stage 4, the volume concentration of the ethanol aqueous solution is 70%, the treatment time is 2 h, and the treatment temperature is 30° C.;

[0155] In stage five, the volume concentration of the ethanol aqueous solution is 90%, the treatment time is 2 h, and the treatment temperature is 30° C.;

[0156] The volume concentration of the ethanol aqueous solution in stage six is ​​100%, the treatment time is 2 hours, and the treatment temperature is 30°C;

[0157] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 2 KPa and a temperature of 37°C for 8 hours to obtain a high-strength regenerated silk fibroin material.

[0158] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.25GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

[0159] Example 8

[0160] A method for preparing a high-strength regenerated silk fibroin material, the specific steps are as follows:

[0161] (1) Prepare raw materials:

[0162] SF solution: concentration is 10wt%, solvent is deionized water;

[0163] Ru solution: concentration is 0.03 mol / L, the solvent is deionized water;

[0164] SPS solution: concentration is 0.3 mol / L, the solvent is deionized water;

[0165] Ethanol aqueous solution;

[0166] (2) Preparation of chemically cross-linked silk fibroin hydrogel:

[0167] After Ru solution and SPS solution were added to SF solution in sequence, the visible light intensity was 20 mW / cm 2 , curing under visible light at 37°C for 5 minutes to obtain a chemically cross-linked silk fibroin hydrogel with a compression modulus of 4 KPa;

[0168] Among them, the volume ratio of SF solution concentration to Ru solution is 100:1, and the volume ratio of Ru solution to SPS solution is 1:0.8;

[0169] (3) Preparation of high-strength regenerated silk fibroin:

[0170] The chemically cross-linked silk fibroin hydrogel was treated in stages with an ethanol aqueous solution. The volume ratio of the chemically cross-linked silk fibroin hydrogel to the ethanol aqueous solution in each stage was 1:10, and the concentration of the ethanol aqueous solution in each stage was fixed:

[0171] In stage 1, the volume concentration of the ethanol aqueous solution is 10%, the treatment time is 3 h, and the treatment temperature is 37°C;

[0172] In stage 2, the volume concentration of the ethanol aqueous solution is 80%, the treatment time is 3 h, and the treatment temperature is 37°C;

[0173] After the staged treatment is completed, vacuum drying is carried out at an ambient pressure of 1 KPa and a temperature of 25°C for 8 hours to obtain a high-strength regenerated silk fibroin material.

[0174] The high-strength regenerated silk protein material finally obtained has a compression modulus of 0.2GPa and has a double cross-linked network structure, which is composed of a silk chemical cross-linked network and a β-folded structure physical cross-linked network entangled with each other.

Claims

1. A method for preparing a high-strength regenerated silk fibroin material, characterized in that: The chemically cross-linked silk fibroin hydrogel is sequentially subjected to gradient alcohol treatment and vacuum drying treatment to obtain a high-strength regenerated silk fibroin material, wherein the gradient alcohol treatment refers to a staged treatment with an ethanol-water solution, the concentration of the ethanol-water solution in each stage is fixed, and the concentration of the ethanol-water solution in different stages increases with the increase of the stage number.

2. The method for preparing a high-strength regenerated silk fibroin material according to claim 1, characterized in that: The compression modulus of chemically cross-linked silk fibroin hydrogel is ≥1KPa, and the compression modulus of high-strength regenerated silk fibroin material is ≥0.2GPa.

3. The method for preparing a high-strength regenerated silk fibroin material according to claim 1, characterized in that: The staged treatment is divided into at least two stages, the volume concentration of the ethanol aqueous solution is 10% to 100%, the treatment time of each stage is 1 to 3 hours, and the treatment temperature is 25 to 37°C.

4. The method for preparing a high-strength regenerated silk fibroin material according to claim 3, characterized in that: The volume ratio of chemically cross-linked silk fibroin hydrogel to ethanol aqueous solution is 1:10-50 in each stage.

5. The method for preparing a high-strength regenerated silk fibroin material according to claim 1, characterized in that: The temperature of vacuum drying treatment is 25-37°C, the air pressure is ≤2KPa, and the time is 8-24h.

6. The method for preparing a high-strength regenerated silk fibroin material according to claim 1, characterized in that: The preparation process of chemically cross-linked silk fibroin hydrogel is as follows: after adding LAP solution into SFMA solution, UV light is used to cure the solution into gel, thereby obtaining chemically cross-linked silk fibroin hydrogel.

7. The method for preparing a high-strength regenerated silk fibroin material according to claim 6, characterized in that: The concentration of SFMA solution is 10-20wt%, the concentration of LAP solution is 2wt%, the mass ratio of SFMA solution to LAP solution is 1:0.1-0.3, the UV curing time is 2-5min, and the UV intensity is 20-50mW / cm 2 , the curing temperature is 25 ~ 37 ℃.

8. The method for preparing a high-strength regenerated silk fibroin material according to claim 1, characterized in that: The preparation process of chemically cross-linked silk fibroin hydrogel is as follows: after adding Ru solution and SPS solution to SF solution in sequence, the solution is cured into gel by visible light to obtain chemically cross-linked silk fibroin hydrogel.

9. The method for preparing a high-strength regenerated silk fibroin material according to claim 8, characterized in that: The concentration of SF solution is 10-20wt%, the concentration of Ru solution is 0.03-0.07mol / L, the concentration of SPS solution is 0.3-0.7mol / L, the volume ratio of SF solution concentration to Ru solution is 20-100:1, the volume ratio of Ru solution to SPS solution is 1:0.8-1.2, the time of visible light curing to glue is 5-30min, and the visible light intensity is 20-50mW / cm 2 , the curing temperature is 25 ~ 37 ℃.

10. A high-strength regenerated silk fibroin material prepared by the method for preparing a high-strength regenerated silk fibroin material according to any one of claims 1 to 9, characterized in that: The double cross-linked network structure is formed by the entanglement of a silk chemical cross-linked network and a β-folded structure physical cross-linked network.

Citation Information

Patent Citations

  • Preparation method and application of silk fibroin and chitin blended nanofiber embedded hydrogel cartilage biomimetic scaffold

    CN109999227A

  • Regenerated silk fibron solution prepared by treating with an ionic reagent

    CA2723241A1

  • Preparation method for regenerated fibroin fiber

    CN102181957A

  • Bi-network high-intensity fibroin hydrogel and preparation method thereof

    CN106146865A

  • Silk fibroin block material and preparation method thereof

    CN108409992A

Cited By

  • High-strength and high-toughness silk fibroin-based material as well as preparation method and application thereof

    CN120757812A

  • High-strength high-toughness silk fibroin-based material and preparation method and application thereof

    CN120757812B